2012
DOI: 10.1210/en.2011-2160
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Synthetic Glucocorticoid Treatment Changes DNA Methylation States in Male Organ Systems: Multigenerational Effects

Abstract: Prenatal synthetic glucocorticoids (sGC) are administered to pregnant women at risk of delivering preterm, approximately 10% of all pregnancies. Animal studies have demonstrated that offspring exposed to elevated glucocorticoids, either by administration of sGC or as a result of maternal stress, are at increased risk of developing behavioral, endocrine, and metabolic abnormalities. DNA methylation is a covalent modification of DNA that plays a critical role in long-lasting programming of gene expression. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 63 publications
7
114
0
3
Order By: Relevance
“…Furthermore glucocorticoid exposure is associated with both methylation and demethylation of promoter and enhancer regions, illustrating a potentially complex regulatory pathway (Crudo et al, 2013;Thomassin et al, 2001). Crudo et al (2012) demonstrated that the endogenous glucocorticoid surge alters the expression of methylation specific genes such as DNA (cytosine-5)-methyltransferase 3b and methyl-CpG-binding domain protein 2 and is instrumental in defining DNA methylation patterns in an organ-specific manner (Crudo et al, 2012). The effects of glucocorticoids on methylation patterns are long lasting and are sustained into adulthood and even in subsequent generations (Crudo et al, 2012(Crudo et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore glucocorticoid exposure is associated with both methylation and demethylation of promoter and enhancer regions, illustrating a potentially complex regulatory pathway (Crudo et al, 2013;Thomassin et al, 2001). Crudo et al (2012) demonstrated that the endogenous glucocorticoid surge alters the expression of methylation specific genes such as DNA (cytosine-5)-methyltransferase 3b and methyl-CpG-binding domain protein 2 and is instrumental in defining DNA methylation patterns in an organ-specific manner (Crudo et al, 2012). The effects of glucocorticoids on methylation patterns are long lasting and are sustained into adulthood and even in subsequent generations (Crudo et al, 2012(Crudo et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Crudo et al (2012) demonstrated that the endogenous glucocorticoid surge alters the expression of methylation specific genes such as DNA (cytosine-5)-methyltransferase 3b and methyl-CpG-binding domain protein 2 and is instrumental in defining DNA methylation patterns in an organ-specific manner (Crudo et al, 2012). The effects of glucocorticoids on methylation patterns are long lasting and are sustained into adulthood and even in subsequent generations (Crudo et al, 2012(Crudo et al, , 2013. In the present study, we found that treatment with dexamethasone was not associated with changes in global DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, these effects were resolved in the F3 generation [18]. Experimental models in the guinea pig (maternal DEX and low-protein diet) have shown DNA methylation changes, altered hypothalamic-pituitary axis function and cardiovascular impairment as well as delayed neurodevelopment in the F2 offspring [25,26]. Maternal diets deficient in micronutrients have also been shown to result in F2 phenotypes including vitamin D and zinc deficiencies [27,28,29].…”
Section: Animal Modelsmentioning
confidence: 99%
“…A transgenerational effect of the epigenetic changes has also been proposed. The second-generation offspring (F2) of guinea pigs treated during pregnancy with multiple doses of betamethasone showed reduced methylation of genomic DNA globally and of specific genes involved in the methylation process per se [49, 87]. …”
Section: Epigenetics and Early-life Gc Exposurementioning
confidence: 99%